Der „Reichtum“ der Korinther und die paulinische Kollekte: 2 Kor 8–9 und die Frage der sozial-ökonomischen Zusammensetzung der korinthischen Gemeinde - Wojtkowiak, Heiko (Novum Testamentum, 2023)
In studies of the socio-economic composition of the church in Corinth, 2 Cor 8–9 are rarely considered. However, it is precisely these chapters that are instructive, since Paul addresses the entire community with a financial need, and, in order to succeed, the economic situation of the whole community must be taken into account. In these chapters, the apostle justifies and motivates his plea with reference to the material abundance of his audience and assumes that all church members are able to participate in giving. This supports the thesis, which is widespread in recent research, that the community is not primarily made up of the lowest, but rather the middle, and perhaps upper, social classes.